The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/anie.201601136
|View full text |Cite|
|
Sign up to set email alerts
|

Benzimidazobenzothiazole‐Based Bipolar Hosts to Harvest Nearly All of the Excitons from Blue Delayed Fluorescence and Phosphorescent Organic Light‐Emitting Diodes

Abstract: Much effort has been devoted to developing highly efficient organic light-emitting diodes (OLEDs) that function through phosphorescence or thermally activated delayed fluorescence (TADF). However, efficient host materials for blue TADF and phosphorescent guest emitters are limited because of their requirement of high triplet energy levels. Herein, we report the rigid acceptor unit benzimidazobenzothiazole (BID-BT), which is suitable for use in bipolar hosts in blue OLEDs. The designed host materials, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 44 publications
(14 reference statements)
1
56
0
Order By: Relevance
“…Notably, using 4CzPNPh [15a] as the yellow TADF dopant, a record high EQE of 22.5% was obtained, much higher than the 9.9% EQE obtained using mCP as the host. Cui et al reported two benzimidazobenzothiazole‐based hosts, 29Cz‐BID‐BT and 39Cz‐BID‐BT , (Figure ). These hosts possessed high triplet energies (>3.0 eV) and favor ambipolar charge transport.…”
Section: Development Of Host Materials For Tadf Devicesmentioning
confidence: 99%
“…Notably, using 4CzPNPh [15a] as the yellow TADF dopant, a record high EQE of 22.5% was obtained, much higher than the 9.9% EQE obtained using mCP as the host. Cui et al reported two benzimidazobenzothiazole‐based hosts, 29Cz‐BID‐BT and 39Cz‐BID‐BT , (Figure ). These hosts possessed high triplet energies (>3.0 eV) and favor ambipolar charge transport.…”
Section: Development Of Host Materials For Tadf Devicesmentioning
confidence: 99%
“…Bipolar charge transport is also needed for high emission efficiency and ensuring low efficiency roll-off. Thus, a disruption of the p-conjugation-based connectivity between the donor and acceptor units by insulating, saturated atoms (sp 3 -hybridized C or Si) or a twisted p-conjugated spacer is favorable 154 for maintaining a triplet energy level and blocking of intramolecular electronic coupling, yet negatively effects carrier transport properties. 155 The role of the host specifically serves to separate the emitting species to reduce the concentration of high energy excited state species to reduce loss processes through photophysical processes, notably triplet-triplet annihilation, 19,136 and device efficiency, i.e.…”
Section: Carbazole-based Materials As Tadf Emittersmentioning
confidence: 99%
“…An ideal host material for yellow‐to‐red TADF yellow emitters should have: (1) sufficiently high singlet and triplet state energies for exciton confinement; (2) appropriate highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels to avoid charge trapping on the emitter and to facilitate charge transport through the device; (3) broad spectral overlap with the emitters for efficient Förster energy transfer; and (4) ambipolar character to facilitate charge transport and carrier injection . To satisfy these requirements, the choice of building segments and the connectivity of the host should be carefully considered.…”
Section: Introductionmentioning
confidence: 99%